(untitled) (Global Journal of Human-Social Science, 2024)
The peculiarities of the political perception of the phenomenon of "blooming complexity" are analyzed, which is actualized in the theory of the processuality of natural development in the teachings of K. Leontiev. An attempt is made to conceptualize the political foundations of the "blooming complexity" phenomenon. The basic scientific problem is the identification of characteristic features of the second phase -"blooming complexity", which fits into the triadic system of the birth, establishment and decline of states and civilizations in the theory of K. Leontiev. The results of the study are representative of the characteristics of the political features of each period of the system: primary simplicity, flourishing complexity, secondary confusing simplification -which appear in homologous unity and historically encapsulate a certain statecivilization in the general historical context.